2022
DOI: 10.3897/neobiota.78.89673
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and morphology of the invasive legume Lupinus polyphyllus along a latitudinal gradient in Europe

Abstract: Plant phenology, i. e. the timing of life cycle events, is related to individual fitness and species distribution ranges. Temperature is one of the most important drivers of plant phenology together with day length. The adaptation of their phenology may be important for the success of invasive plant species. The present study aims at understanding how the performance and the phenology of the invasive legume Lupinus polyphyllus vary with latitude. We sampled data across a >2000 km latitudinal gradient fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Concerning temporal patterns, observations of L. polyphyllus clearly followed its phenological cycle (Ludewig et al, 2022). It has been shown that temporal patterns in iEcology data follow human interactions with species, for example, for Google searches on ticks in Denmark (Jensen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning temporal patterns, observations of L. polyphyllus clearly followed its phenological cycle (Ludewig et al, 2022). It has been shown that temporal patterns in iEcology data follow human interactions with species, for example, for Google searches on ticks in Denmark (Jensen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, studies on the latitudinal distribution of species can give valuable information on their climatic niches and are crucial to predict future range shifts under a warming climate. Despite their relevance, empirical phenological studies across large geographical scales are limited (but see Ludewig et al, 2022; Nordt et al, 2021). This is mainly because such studies require frequent simultaneous observations across different latitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lupinus polyphyllus is a perennial plant of the family Fabaceae, which is native to North America and was intentionally introduced to Europe as an ornamental plant in the 19th century [6]. The species quickly spread, especially in ruderal habitats (roadsides, wastelands, degraded areas) and semi-natural habitats, such as meadows, grasslands, and forest edges.…”
Section: Research Areas and Objectsmentioning
confidence: 99%
“…One of the widespread invasive species that threatens the biological richness of mountain meadows and grasslands is Lupinus polyphyllus Lindl., also known as garden lupin or large-leaved lupine. By creating dense patches and producing allelopathic substances, this species may limit the germination of native plants and be harmful to farm animals, which is why it was chosen as the subject of this study [6,7].…”
Section: Introductionmentioning
confidence: 99%